Colistimethate sodium is efficacious and safe for the management of sepsis in hematological diseases patients: a retrospective study in China - Xie, Yan; Liu, Ziyi; Liang, Peiqi; Wang, Dong; Li, Qian; Gao, Meng; Kong, Jindan; Wu, Depei; Qi, Jiajun; Xu, Jie; Fu, Jianhong (Frontiers in Cellular and Infection Microbiology, 2025)
PurposePatients afflicted with hematological diseases are at an elevated risk of infection, with the potential for the development of sepsis. This study aims to analyze the effectiveness and safety of colistimethate sodium (CMS) in the management of sepsis in Chinese patients with hematological diseases.MethodsA retrospective study was conducted on hematological diseases patients diagnosed as sepsis and treated with CMS at the First Affiliated Hospital of Soochow University between November 2021 and July 2023. Demographics, clinical presentation, causative organisms, clinical outcomes and adverse events (AEs) were recorded. The univariate and multivariate analysis was conducted to identify predictive factors for clinical effectiveness and renal insufficiency.ResultsA total of 81 hematological patients diagnosed with sepsis were included, the mean (change in sequential organ failure assessment [SOFA] score) ΔSOFA when utilizing CMS was 3.90 ± 2.10. Following CMS treatment, a clinical effectiveness rate was observed in 62.96% of patients, while the bacteriological eradication rate was 60.23%. Additionally, the 28-day all-cause mortality rate was 29.63%. The median length of stay in the ICU and total in-hospital stay was 13.5 and 33 days, respectively. AEs were reported in 16 patients (19.75%), including 15 (18.52%) renal insufficiency, 1 (1.23%) hepatic insufficiency, and 1 (1.23%) rash. The multivariate analysis of clinical effectiveness indicated that a higher Acute Physiology and Chronic Health Evaluation (APACHE) II score, a higher Charlson comorbidity index, the relapse or refractory of hematological diseases, septic shock, and the use of mechanical ventilation was independently associated with a poor clinical effectiveness. The univariate analysis of renal insufficiency demonstrated that allogeneic hematopoietic stem cell transplantation, aplastic anemia, and gastrointestinal infection had a statistically significant impact on renal function.ConclusionsThe findings of our study demonstrated that CMS was an efficacious treatment for sepsis in Chinese patients with hematological diseases, while concurrently exhibiting an acceptable toxicity profile.